Holographic prism projection: extinction rebellion & energy futures on sci-fi television - Kerr, Thor; Grenfell, Raymond; Rahaman, Hafizur; Boyle, Maureen; Eames, Richard (Taylor and Francis Group, 2023)
This study in media practice provides insights on video production for holographic prism projection, which has become more accessible as smart flat screens have become more available. The study reflects on the experiences of producing, installing and viewing a documentary video projected via holographic prism, titled ‘FarNearFutureNow.’ Engaging the participation of Extinction Rebellion (XR) members, this university-funded production included recording and combining interview footage with energy policy texts in the visual style of the hologram scene from Star Wars, the 1977 science-fiction film. With viewer co-experience, environmental politics and legacies of colonialism in mind, we produced a 5-minute video and prism projection system for public exhibition. FarNearFutureNow was produced through collective processes of gathering, assembling, reviewing, storyboarding, scripting and editing interview footage and other recordings as well as testing and fabricating installation materials. These production processes enabled us to understand the affordances of creative darkness in holographic production for disassociating and recombining visual elements. The hologram’s disassociated focus on a single object proved useful in drawing audience attention and for assembling non-fiction elements in sequences referencing popular fiction. It is also useful for showing radically different visual scales in sequence, and for simultaneously juxtaposing audio and visual scales.